LAW ENFORCEMENT THROUGH THE PRINCIPLE OF GOOD FAITH IN THE PRE-CONTRACT PHASE ACCORDING TO INDONESIAN CIVIL LAW - Onny Medallions; Ida Nadirah (Journal of Islamic, Social, Economics and Development, 2023)
Faith Good is something abstract and difficult meaning For formulated , deep implementation agreement faith Good become something principle related with problem propriety and appropriateness . obscurity principle faith Good Already felt important confirm Good in circles academics nor practitioner including the judges who decide dispute civil proceedings in court . Moreover in law sourced Indonesian civil law from the Civil Code No explain more detail When commencement principle faith Good in something agreement is it in phase implementation contract or principle faith Good can started since phase pre contract . With development law contract moment this , in phase pre contract sometimes Already happen event law that causes loss party in that will carry out agreement . this writing discuss about position principle faith Good in phase pre linked contract with system enforcement law in effort upright function upright norms law in a manner real as guidelines behavior in connection law . Analysis results from wrote this, system enforcement law This can reviewed from corner subjective and angular objective . As public as subject law from beginning in preprocessing _ contract has can apply principle obedience and honesty to what already _ become agreement early, though That Not yet poured in agreement written . Where did it happen dispute Civilization in pre- era contract , then here demanded the role of the Judge in give evaluation application principle faith Good as position strategic in realize enforcement law agreement i.e. through development understanding faith Good in activity invention impact law _ to system enforcement law . Development law Indonesian civil law , regulation principle faith Good it turns out Already enter in a number of design regulation legislation, for example in script Academic Contract Law Bill, manuscript Academic Bill of Civil Procedure Law, manuscript academic Bill on Commercial Law, Land Bill and so on